The Intergenerational Transmission of Teaching - Alberto Jacinto; Seth Gershenson (Institute of Labor Economics (IZA), 2019)
Parental influences, particularly parents' occupations, may influence individuals' entry into the teaching profession. Importantly, this mechanism may explain the relatively static demographic composition of the teaching force over time. We assess the role of parental influences on occupational choice by testing whether the children of teachers are disproportionately likely to become teachers themselves and whether the intergenerational transmission of teaching varies by race or sex. Overall, children whose mothers are teachers are 9 percentage points (or more than two times) more likely to enter teaching than the children of non-teacher mothers. This rate of occupational transmission is significantly larger than for several comparable professions. The transmission of teaching from mother to child is about the same for white children of both sexes and for black daughters; however, transmission rates for Hispanic daughters are even larger while those for black sons are about zero. Limited data on father's occupation suggests that sons whose fathers are teachers are more likely to enter the profession than the sons of non-teachers, though there is no such effect for daughters.
Keywords: I20; J62; J45; 330; intergenerational mobility; occupational choice; teacher labor supply